EFFECT OF NATURAL FEEDING ON THE GROWTH OF SNAKEHEAD FISH (Channa maruliodes) - Putri, Melani; Hidayati, Sri; Armando, Eric (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
The obstacle faced by snakehead fish farmers is the provision of feed that has quality and a high protein content for the growth period of fish. Natural feed can be an alternative. The purpose of this study was to determine the effect of the natural feeding of gold snails, earthworms, and Hongkong caterpillar types on the growth of snakehead fish. The research was conducted from January to February 2022, in Adipasir Village RT. 07 RW. 02 Rakit District, Banjarnegara Regency, Central Java. The method used in this study was experimentally arranged using a completely randomized design (CRD). This study consisted of 4 treatments with 4 replications and each treatment consisted of 5 snakehead fish so the number of containers used was 16 pieces and 80 snakehead fish. The analysis used was a one-way Analysis of Variance (ANOVA) with an error level of α = 0.05. The treatment consisted of T1 (control with Pellet), T2 (gold snail), T3 (earthworms), and T4 (Hongkong Caterpillars). The results showed that natural feeding influences the growth of snakehead fish. The best treatment is natural food in the form of a Hongkong caterpillar with an absolute weight of 4.7475 g, an absolute length of 3.63 cm, FCR of 1.07.